Cytotoxic abietane-type diterpenoids from twigs and leaves of Croton laevigatus. (December 2017) - Song, Jin-Tong; Liu, Xiao-Yu; Li, Ai-Ling; Wang, Xiao-Ling; Shen, Tao; Ren, Dong-Mei; Lou, Hong-Xiang; Wang, Xiao-Ning
Graphical abstract: Highlights: Seven new abietane-type diterpenoids were obtained from Croton laevigatus . Another new aromatic compound, hexyl Z -ferulate was also obtained. The structures were determined by extensive spectroscopic analysis. Compounds2, 7, and10 showed cytotoxicity against cancer cells. Abstract: Seven new abietane-type diterpenoids, crotolaevigatones A–G (1 –7 ), one new aromatic compound, hexyl Z -ferulate (8 ), along with three known diterpenoids (9 –11 ) and one known aromatic ester, hexyl E -ferulate (12 ), were obtained from the twigs and leaves of Croton laevigatus . The structures of all isolated compounds were established on the basis of extensive NMR and MS spectroscopic analyses. Compounds2 and7 exhibited weak anti-proliferative activity against the A549 and MDA-MB-231 cancer cells, while compound 10 selectively showed significant inhibitory activity against the A549 cancer cells.